2004
DOI: 10.1073/pnas.0407076101
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiota as an environmental factor that regulates fat storage

Abstract: New therapeutic targets for noncognitive reductions in energy intake, absorption, or storage are crucial given the worldwide epidemic of obesity. The gut microbial community (microbiota) is essential for processing dietary polysaccharides. We found that conventionalization of adult germ-free (GF) C57BL͞6 mice with a normal microbiota harvested from the distal intestine (cecum) of conventionally raised animals produces a 60% increase in body fat content and insulin resistance within 14 days despite reduced food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

128
4,329
8
176

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 5,344 publications
(4,767 citation statements)
references
References 31 publications
128
4,329
8
176
Order By: Relevance
“…Along the same lines Bäckhed et al (2004), recently reported that germ-free mice re-colonized with normal microbiota rapidly develop a 60% increase in body fat mass associated with insulinresistance, despite reduced food intake. As expected (Maffei et al, 1995), these mice present increased leptin levels, proportional to the increase of body fat.…”
Section: Iii1b : Microflora Composition Is Influenced By Nutritionmentioning
confidence: 79%
“…Along the same lines Bäckhed et al (2004), recently reported that germ-free mice re-colonized with normal microbiota rapidly develop a 60% increase in body fat mass associated with insulinresistance, despite reduced food intake. As expected (Maffei et al, 1995), these mice present increased leptin levels, proportional to the increase of body fat.…”
Section: Iii1b : Microflora Composition Is Influenced By Nutritionmentioning
confidence: 79%
“…A novel role in regulating fat storage has been recently ascribed to microbiota by recent studies, a promotion of monosaccharides absorption from the gut resulting in induction of de novo hepatic lipogenesis has been shown by comparing germ-free mice with conventionalised mice (Bä ckhed et al, 2004). Furthermore, an increased capacity to harvest energy from the diet has been observed by comparing gut microbiota of obese and lean mice (Turnbaugh et al, 2006).…”
Section: Gut Bacteria and Healthmentioning
confidence: 99%
“…Plusieurs études américaines émanant du laboratoire de J. Gordon ont suggéré l'implication de la flore intestinale dans la régulation de l'homéostasie énergétique [11]. Il y a quelques années, F. Backhed et ses collaborateurs ont mis en évidence le fait suivant : de jeunes souris élevées de façon classique possèdent -malgré un apport alimentaire en calories moins important -une masse adipeuse plus développée (+ 40 %) que celle des souris exemptes de flore intestinale (souris axéniques) [12]. Dans le même ordre d'idée, les auteurs ont démontré que les souris dépourvues de flore intestinale à la naissance, puis colonisées avec une flore intestinale émanant de souris normales, développent davantage de masse grasse (environ + 60 %) et présentent une diminution de la sensibilité à l'insuline deux semaines après l'instauration de la flore.…”
Section: La Flore Intestinale De L'homme : Un Jardin Secretunclassified
“…La diminution de l'expression de FIAF observée chez les souris colonisées, participerait à l'accumulation de lipides dans le tissu adipeux. Ces expériences ont démontré pour la première fois que les bactéries intestinales pouvaient réguler le stockage d'énergie chez l'hôte qu'elles colonisent [12] ( Figure 1). …”
Section: Extraction Et Absorption De L'énergie Non Digéréeunclassified